Active CMV infection in two patients with multiple sclerosis treated with alemtuzumab. (May 2017) - Clerico, Marinella; De Mercanti, Stefania; Artusi, Carlo Alberto; Durelli, Luca; Naismith, Robert T
Alemtuzumab is a humanized monoclonal antibody targeting the surface molecule CD52, resulting in a rapid depletion of innate and adaptive immune cells. Infection rates in multiple sclerosis (MS) treatment trials were higher in alemtuzumab than in interferon beta–treated patients. We report two MS patients who developed cytomegalovirus disease within 1 month after the first 5-day cycle of alemtuzumab. Upon identification and appropriate treatment of the infection, each recovered completely. Neurologists should be aware of this serious but treatable complication.